Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

2x + 5y = 6
2x = 10 – 3y

Solve the simultaneous equations by substitution

(Sorry all my questions are maths i suck, more to come)


Sagot :

Step-by-step explanation:

Given equations

2x + 5y = 6 .......i)

2x = 10 - 3y...... II)

Putting 2x = 10 - 3y in equation i

10 - 3y + 5y = 6

2y = 6 - 10

2y = - 4

y = - 4 / 2

y = - 2

Now putting y = - 2 in equation ii

2x = 10 - 3 * ( - 2)

2x = 10 + 6

2x = 16

x = 16 / 2

x = 8

So x = 8 and y = - 2

Hope it will help :)❤

We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.